How Dentists Read a Technique Article: A Grounded Theory Investigation. Issue 8 (4th November 2016) - Chambers, David W.; Lyon, Lucinda J.
Abstract: Purpose: To conduct an empirical investigation using qualitative techniques of the way dentists engage in the process of reading a technique‐oriented journal article and what they pay attention to in the process. Materials and Methods: Grounded theory was used to identify how dentists read an article describing the fabrication of an interim prosthesis in the esthetic zone. Twenty‐one experienced practitioners were videotaped, and their verbatim reflections were coded. The sequence of attending to various features of the paper was noted. Results: Ninety‐five percent of readers voiced specific, multiple attempts to identify or refine the main purpose of the article as they processed the material. All readers engaged in various activities to navigate through the article, including skipping and backtracking, and none "read" the article straight through. All readers also made repeated observations about the relevance of the technique to their personal practice situation. Eighty percent used some form of "distancing, " whereby the content and value of the article were accepted, but the reader reserved the privilege of not being bound by the results because of technical, sponsorship, or methodological issues that "might be present." The quality of photographs was accepted as a proxy for the quality of technical work performed. Conclusions: Dentists actively customized the reading of a journal article that described a technical procedure. They imposed a non‐linear structure for absorbing information and a standard of personal relevance, and, while accepting the results, created reasons for not necessarily having to accept them as applicable. The approach clinicians use in reading a procedural article may be different from the structure writers use in preparing a paper.